Evaluation of ultrasonic axillary dissection in preservation of intercostobrachial nerve and lymphatic sealing in breast cancer patients: Randomized controlled trial. (December 2020) - Salama, Ahmed M.F.; Nawar, Ahmed M.; Zayed, Mohamed E.; Essa, Mohamed S.
Abstract: Background: Electrocautery has been shown to be associated with excessive serous drainage which may lead to many complications in patients with breast cancer needing dissection of the axillary lymph nodes. The Harmonic Focus could outperform electrocautery in dissection of axillary lymph nodes, resulting in shortening of the operative times and minimize postoperative complications. This study aims to compare the mean axillary drain production and the axillary numbness frequency in axillary lymph node dissection (ANLD) during Modified Radical Mastectomy (MRM) and breast conservative surgery (BCS) between the use of harmonics scalpel and electrocautery. Methods: This study includes 40 patients presented with early breast cancer (T1 and T2) underwent BCS or MRM in general surgery department, Faculty of Medicine, Benha University Hospital during the period from January 2017 to September 2019. The patients randomly assigned into 2 groups; group A: subjected to ANLD using Harmonic Focus tool and group B: subjected to ANLD using electrocautery. Operative time, total drainage volume, blood loss, duration of the drain and frequency of axillary numbness were recorded. Results: This study shows that using Harmonic in axillary dissection considerably reduced operating time, total drainage volume, blood loss, days of hospital stays and reduced axillary numbness level in comparison to conventional electrocautery. Conclusion: Compared to the normal electrocautery, the harmonic focus dissection has major advantages in lowering postoperative drainage, blood loss intra-operative and lower incidence of axillary numbness in breast cancer axillary dissection, without affecting operating time. Highlights: Use of Harmonic Focus associated with decrease in blood loss and operative duration. Use of Harmonic focus also associated with decreases the total axillary drain output, the drain duration. Harmonic Focus reduce frequency of axillary numbness.